2011
DOI: 10.1177/1756285611405565
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis and chronic cerebrospinal venous insufficiency: a critical review

Abstract: Chronic cerebrospinal venous insufficiency (CCSVI) was recently proposed as a contributing factor in the pathology of multiple sclerosis. This concept has gained remarkable attention, partly because endovascular neurointervention has been suggested as a treatment strategy. This review summarizes available evidence and provides a critical analysis of the published data. Currently, there is inconclusive evidence to support CCSVI as an etiological factor in patients with multiple sclerosis. Endovascular procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…hronic cerebrospinal venous insufficiency (CCSVI), a sonography-defined pattern of cerebral venous drainage, has been reported in a variable proportion of adults with multiple sclerosis (reviewed in Awad et al 1 and Laupacis et al 2 ). A combination of findings of altered venous flow, venous stenoses with presumed secondary venous drainage patterns (termed "excision circles"), or reflux in extracranial draining veins led to the term CCSVI.…”
mentioning
confidence: 99%
“…hronic cerebrospinal venous insufficiency (CCSVI), a sonography-defined pattern of cerebral venous drainage, has been reported in a variable proportion of adults with multiple sclerosis (reviewed in Awad et al 1 and Laupacis et al 2 ). A combination of findings of altered venous flow, venous stenoses with presumed secondary venous drainage patterns (termed "excision circles"), or reflux in extracranial draining veins led to the term CCSVI.…”
mentioning
confidence: 99%
“…There has also been a problem with consistency. Studies conducted afterwards failed to reproduce the results found by Zamboni [6]. A potential explanation of this lack of consistency could be due to inadequate methods.…”
Section: Chronic Cerebrospinal Venous Insufficiency (Ccsvi)mentioning
confidence: 90%
“…Zamboni's publications, detailing the findings of vascular anomalies in MS patients and purporting CCSVI as a cause of MS, however alluring, were treated with skepticism in the scientific community due to the lack of a double-blind randomized control normally required for clinical trials. In surveys, such as the one conducted by Zamboni, the Hill Criteria can be used to infer causality [6]. Criteria on the Hill checklist include temporality and consistency.…”
Section: Chronic Cerebrospinal Venous Insufficiency (Ccsvi)mentioning
confidence: 99%
See 2 more Smart Citations